The Impact of the Aukus Trilateral Security Pact on South Pacific Regional Security - Yulia Rimapradesi; Bagaskara Sagita Wijaya; Zulfa Karima (Journal of Islamic World and Politics, 2023)
The AUKUS Trilateral Security Pact is a form of collective security cooperation, and this study examines its effects on South Pacific regional security. To stabilize regional security in the South Pacific, which is a main target of China’s maritime ambitions, the authors emphasize the urgency of AUKUS’s presence. To shed light on the issue, the authors used the collective security concept to dissect the framework of cooperation, the motives of AUKUS, and the Security Dilemma concept to explain how geopolitical shifts affect the security stability of the South Pacific. This research employed qualitative methods with an explanatory type of research. In this type of research, the formulated hypothesis was tested to see how the variables under study affected one another. According to this research’s findings, AUKUS’s approach to military confrontation as a partnership for collective security actually encourages an aggressive coalition and poses a security risk, thereby increasing the likelihood of further conflict in the South Pacific region.